DEFINITION OF CRIMINAL AND ILLEGAL ACTIVITIES IN THE ECONOMIC SPHERE - Serhii Vitvitskyi; Anton Syzonenko; Tetiana Titochka (Baltic Journal of Economic Studies, 2022)
The purpose of the article is to define the essence of criminal and illegal activities in the field of economy; to clarify its determinants; to highlight the features of national prevention of socially dangerous acts that threaten the economic security of the state. The scientific discussion is presented, which highlights the problem of determining the markers of illegal activity in the field of economy. Such markers include: 1) the investigated criminal offenses always create a platform for the "shadow" economy; 2) criminal offenses in the field of economy are interconnected with corruption, which simplify such illegal activities (the subjects of criminal offenses in the field of economy are usually officials); 3) the presence of intent to obtain economic benefits; 4) the presence of only direct intent; 5) illegal actions are committed by all possible criminal means. The causes and conditions of criminal and illegal activities in the sphere of economy are determined. The groups of factors of criminal and illegal activities in the sphere of economy are considered. It is noted that mistakes in economic planning inevitably result in artificial (often unintentional) formation of conditions conducive to the commission of illegal acts. Socio-economic causes are retrospective in nature, i.e., they are historically conditioned phenomena associated with economic changes, the latter occurring over the past fifty years. Some national means of preventing socially dangerous acts in the economic sphere are proposed. Results. The author's approach to the concept of criminal illegal activity in the field of economy is proposed. The complex of reasons and conditions of criminal and illegal activity in the sphere of economy is developed, which include 1) insufficient level of social protection of the population; 2) unsatisfactory level of economic development of the state; 3) inconsistency of the mentality of the society with the social values recognized at the highest state level; 4) the presence of "dead" zones in the labor market; 5) insecurity of small and medium-sized businesses in the state, etc. It is found that the measures and means of national prevention of criminal illegal activities in the sphere of economy should include 1) stabilization of the political situation in the country; 2) solving the problems of small and medium-sized businesses; 3) identification of gaps in economic planning and forecasting of economic measures for the next years; 4) development of the labor market, including the creation of "dead" zones, the continuation of a number of state-owned enterprises; 5) increase the level of social protection of vulnerable categories of the population (elderly people, people with special needs, people raising children on their own, etc.); 6) improve the social package provided to employees; 7) increase the level of average wages, etc.